CRYOGLOBULINS IN UVEITIS - Bosnjakovska S.; Polenakovic B.; Celeva V.; Arnaudovski Z. (SOE 1995, 1995)
The authors examined cryoglobulins in a group of patients with anterior uveils and in a group of patients with posterior uveitis by means of a prospective study. Total cryoglobulins were measured by the method of Lowry - identification of cryoglobulins with oucherlony, Scheidegger and the quantity of the elements of cryoglobulins with the method of Mancini. The authors exam the activity of antigamma globulins with Reuma factor. The purpose of our examination is determination of the cryoglobulin levels in the uveilis with the different aethiology and correlation between the level of the cryoglobulins only as separate form of the illness.